ChemInform Abstract: Enantioselective Synthesis of Coumarin Derivatives Catalyzed by Primary Amines. Issue 16 (22nd April 2014) - Lee, Yen‐Te; Das, Utpal; Chen, Yi‐Ru; Lee, Chia‐Jui; Chen, Chi‐Han; Yang, Mei‐Chun; Lin, Wenwei
Abstract Michael addition reaction of ketones with coumarin derivatives in the presence of cinchona type catalyst provides optically active coumarins with excellent enantioselectivity.